Highly sensitive, selective, and rapid detection of miRNA-21 using an RCA/G-quadruplex/QnDESA probing system. Issue 2 (17th December 2021) - Asa, Tasnima Alam; Ravi Kumara, Guralamatta Siddappa; Seo, Young Jun
Abstract : In this study we developed a very simple and rapid miRNA 21 detection system using a novel QnDESA probe for sensing the 22AG hybrid G-quadruplex with a single-step rolling circle amplification (RCA) reaction. Abstract : In this study we developed a very simple and rapid miRNA 21 detection system using a novel quinolinium diethylamino salicylaldehyde (QnDESA) probe for sensing the 22AG hybrid G-quadruplex with a single-step rolling circle amplification (RCA) reaction. We synthesized a circular DNA padlock template containing a sequence complementary to the 22AG hybrid G-quadruplex, used SplintR ligase to ensure perfect hybridization with miRNA 21, applied this circular DNA and phi-29 DNA polymerase for tandem amplification of the 22AG hybrid G-quadruplex sequence, and then probed the product using QnDESA. This combination of RCA-G-quadruplex and QnDESA allowed the rapid (1 h) and simple one-pot detection of miRNA 21 based on a change in fluorescence. In addition, this system displayed high sensitivity (limit of detection: 1.37 fM) and selectivity. This probing system should also be useful for identifying a diverse range of DNA- and RNA-based biomarkers.